The Curt Flood Story : The Man behind the Myth - Weiss, Stuart L. (Book collections on Project MUSE., 2007)
"Examines Curt Flood's often troubled personal life and explores his possible motives for suing Major League Baseball in 1970. For challenging baseball's reserve system, which he likened to bondage, the St. Louis Cardinals center fielder in time was lionized. But this recognition came at great personal expense"--Provided by publisher